Xylanase activity and T2 (MRI) relationship during lulo la selva P32 ripening process - Dueñas Gómez, Yenny Maritza; Pontificia Universidad Javeriana (2015)
The lulo La Selva P32 is a cross over different kinds of lulo. Though its sensory characteristics improvement, its life span is very short. Due to it is a new kind of lulo, there are not so many studies over the ripening process. In order to understand some softening processes, in this work it is evaluated the xylanase kinetics at the lulo peel during ripening, and the results are correlated with the MRI (Magnetic Resonance Imaging) relaxation time T2. During ripening time, it is observed that the xylanase is one of the enzymes involved in the hydrolysis of the cell wall polymers. In addition, two T2 values regimes were distinguished by the xylanase kinetics. Although the correlation coefficient of 0.82 and p = 0.024 values, the results suggest that T2 weighted MRI can be useful as a non-invasive tool for ripening process monitoring.